Sistema integral de cartera para la Cooperativa de ahorro y crédito “29 de Octubre” en la ciudad de Tulcán. - Chugá Cárdenas, Franklin Mauricio (2014)
The implementation of a comprehensive portfolio system for the 29 de Octubre Savings and Credit Cooperative is an important tool for the entity, enabling greater efficiency in the department's financial operations and improved employee performance in the planning, coordination, and communication of the various functions. Therefore, this proposal determines that the company has not had a tool that would make it possible to improve the cooperative's portfolio. Thus, this initiative is proposed to address the problem. The researcher directly observed the diagnosis of this proposal, applying the deductive-inductive method, which allowed for understanding the characteristics of the topic under investigation. The analytical-synthetic method allowed for analyzing and synthesizing the implementation of the comprehensive portfolio system for the cooperative. The studies conducted in this research will aim to demonstrate the improvement of the cooperative's portfolio department through: It is also mentioned that the comprehensive system will improve each of the cooperative's processes, which will lead to the fulfillment of its objectives and goals.